Psychological Mechanisms Involved in Radicalization and Extremism. A Rational Emotive Behavioral Conceptualization - Trip, Simona; Bora, Carmen Hortensia; Marian, Mihai; Halmajan, Angelica; Drugas, Marius Ioan (Frontiers in Psychology, 2019)
Extremist acts and the process of radicalizations got into researchers’ attention worldwide since 2001. The aim of this paper is to offer a broad image on radicalization and extremist acts and to bring a new perspective for the conceptualization of radicalization. Radicalization is a process of developing extremist beliefs, emotions, and behaviors. The extremist beliefs are profound convictions opposesd to the fundamental values of society, the laws of democracy and the universal human rights, advocating the supremacy of a certain group (racial, religious, political, economic, social etc.). The extremist emotions and behaviors may be expressed both in non-violent pressure and coercion and in actions that deviate from the norm and show contempt for life, freedom, and human rights. A complete inroad to psychological mechanism involved in the process of radicalization is offered in order to have a broad image regarding current research in the field. Starting from this point, a rational emotive and behavioral conceptualization on radicalization has been developed, bringing together all the concepts and knowledge in the field. A complete and clear conceptualization is crucial for developing prevention/intervention programs and good practices in dealing with this process which has been spreading in the past years. The final part deals with directions regarding prevention/intervention programs from a rational emotive and behavioral perspective, and also from the perspective of European policies.